2013
DOI: 10.1074/jbc.m112.422667
|View full text |Cite
|
Sign up to set email alerts
|

Mitoferrin-2-dependent Mitochondrial Iron Uptake Sensitizes Human Head and Neck Squamous Carcinoma Cells to Photodynamic Therapy

Abstract: Background: Here, we investigated whether iron mobilization enhanced photodynamic therapy (PDT)-induced cell killing. Results: Lysosomal iron release and mitochondrial iron uptake through mitoferrin-2 (Mfrn2) acted synergistically to induce PDT-mediated and iron-dependent mitochondrial dysfunction and cell killing. Conclusion: Mfrn2 plays a critical role in transporting iron to mitochondria to enhance PDT. Significance: Head and neck cancers expressing higher Mfrn2 protein levels benefit more from PDT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 35 publications
2
58
0
Order By: Relevance
“…On the other hand, it has been reported that BAF treatment promotes the release of lysosomal iron in hepatocytes (66). Moreover, such a mechanism has been attributed to the fact that BAF is capable of enhancing the cytotoxicity of phthalocyanine 4-PDT (photodynamic therapy) in A431 cancer cells and in human head and neck squamous carcinoma cells via increased mitochondrial iron uptake (67,68). In our study, we found that BAF decreases intracellular iron level, indicated by the increase of the IRP2 protein level (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been reported that BAF treatment promotes the release of lysosomal iron in hepatocytes (66). Moreover, such a mechanism has been attributed to the fact that BAF is capable of enhancing the cytotoxicity of phthalocyanine 4-PDT (photodynamic therapy) in A431 cancer cells and in human head and neck squamous carcinoma cells via increased mitochondrial iron uptake (67,68). In our study, we found that BAF decreases intracellular iron level, indicated by the increase of the IRP2 protein level (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, blockade of MCU with Ru360 attenuated mitochondrial dysfunction caused by iron overload [58]. However, the specific mechanisms involved in this process require further elucidation.…”
Section: Mitochondrial Iron Metabolismmentioning
confidence: 99%
“…Knockdown of MFRN2 decreases mitochondrial iron uptake in human epithelial cell lines (Hung et al, 2013) and its depletion in cultivated mouse fibroblasts reduced heme synthesis and mitochondrial Fe/S cluster assembly . A similar effect was seen upon depletion of MFRN1, indicating that both Mfrn1 and Mfrn2 contribute to mitochondrial iron acquisition in non-erythroid mammalian cells .…”
Section: The Mitochondrial Inner Membrane Transportersmentioning
confidence: 99%